ANALYSIS OF ARCHIPELAGO RELIGION AND CULTURE AFTER ISLAMIZATION IN INDONESIA - Sofian Syaiful Rizal; Hasan Baharun (International Conference on Humanity Education and Society (ICHES), 2022)
ABSTRACTMuslim countries. Furthermore, with the increasing Islamization of the archipelago, this study uses normative research. The type of data used consists of two, primary data and secondary data. Based on the results of the analysis of the data obtained in the field, this study obtained three important findings namely, the first, the growth of Islamic religion and culture does not eliminate local culture. The process of Islamization does not use military force. Peaceful Islamization took place through trade, the arts, marriage, and education. Second, the effort to reconcile religion and culture is a natural thing and has been done for a long time, with evidence that supports it, as Wali Songo spread Islam by entering community customs. All three Indonesian popular cultures combine many Islamic themes and symbols; Therefore, Islam is often regarded as an important cultural resource in Indonesian popular culture. Urf can only be used as one of the arguments in enforcing sharia law if it meets the following criteria: Urf is good (both specific and general, actions and words) and applies in general.Keywords: Religion, Archipelago Culture, and Islamization.